Causes of diarrhea, pneumonia, and septicemia in swine for 1991 submissions to the KSU Veterinary Diagnostic Laboratory - Frank, R.K.; Vorhies, M.W. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Causes of pre- and postweaning diarrhea, pneumonia, and bacterial septicemia in pigs were summarized for fiscal year 1991 (July, 1990 to June, 1991) for submissions to the Kansas State University Veterinary Diagnostic Laboratory. Escherichia coli was the most common cause of both pre- and postweaning diarrhea in pigs (33.5% and 25.0%, respectively, of submissions for diarrhea). Other commonly diagnosed causes included transmissible gastroenteritis (24.4%) and coccidiosis (16.5%) for preweaning diarrhea, and proliferative enteritis (19.2 %) and salmonellosis (13.2 %) for postweaning diarrhea. The most commonly diagnosed causes of pneumonia in nursing, growing, and finishing pigs were Pasteurella multocida, Mycoplasma, and Actinobacillus (Haemophilus) pleuropneumoniae. Streptococcus and Salmonella were common causes of bacterial septicemia in Kansas pigs.
Keywords: Swine; Disease; Diagnosis; Diarrhea; Pneumonia